Disturbance to conserved bacterial communities in the cold‐water gorgonian coral Eunicella verrucosa. Issue 2 (1st September 2014) - Ransome, Emma; Rowley, Sonia J.; Thomas, Simon; Tait, Karen; Munn, Colin B.
Abstract The bacterial communities associated with healthy and diseased colonies of the cold‐water gorgonian coral Eunicella verrucosa at three sites off the south‐west coast of England were compared using denaturing gradient gel electrophoresis (DGGE) and clone libraries. Significant differences in community structure between healthy and diseased samples were discovered, as were differences in the level of disturbance to these communities at each site; this correlated with depth and sediment load. The majority of cloned sequences from healthy coral tissue affiliated with the Gammaproteobacteria. The stability of the bacterial community and dominance of specific genera found across visibly healthy colonies suggest the presence of a specific microbial community. Affiliations included a high proportion of Endozoicomonas sequences, which were most similar to sequences found in tropical corals. This genus has been found in a number of invertebrates and is suggested to have a role in coral health and in the metabolisation of dimethylsulfoniopropionate (DMSP) produced by zooxanthellae. However, screening of colonies for the presence of zooxanthellae produced a negative result. Diseased colonies showed a decrease in affiliated clones and an increase in clones related to potentially harmful/transient microorganisms but no increase in a particular pathogen. This study demonstrates that a better understanding of these bacterial communities, the factors that affect them and their role in coral health and disease will be of critical importance in predicting future threats to temperate gorgonian communities.